A survey of energy drink and alcohol mixed with energy drink consumption. Issue 1 (December 2015) - Magnezi, Racheli; Bergman, Lisa; Grinvald-Fogel, Haya; Cohen, Herman
Abstract Background Energy drink consumption among youth is increasing despite recommendations by the American Academy of Pediatrics to eliminate consumption by youth. This study provides information on consumption of energy drinks and alcohol mixed with energy drinks (AmED) in a sample of Israeli youth and how consumer knowledge about the risks affects consumption rates. Methods The study was conducted in three Tel Aviv public schools, with a total enrollment of 1, 253 students in grades 8 through 12. Among them, 802 students completed a 49-item questionnaire about energy drink and AmED consumption, for a 64 % response rate Non-responders included 451 students who were absent or refused to participate. All students in the same school were administered the questionnaire on the same day. Results Energy drinks are popular among youth (84.2 % have ever drunk). More tenth through twelfth grade students consumed energy drinks than eighth and ninth grade students. Students who began drinking in elementary school (36.8 %) are at elevated risk for current energy drink (P  < .001) and AmED (P  = .002) use. Knowledge about amounts consumed and recommended allowances is associated with less consumption (OR 1.925; 95 %CI 1.18–3.14). Discussion The association between current AmED consumption and drinking ED at a young age is important. Boys and those who start drinking early have a greater risk of both ED and AmED consumption. The characteristics of early drinkers can help increase awareness of potential at-risk youth, such as junior and senior high school students with less educated or single parents. Conclusions Risks posed by early use on later energy drink and AmED consumption are concerning. We suggest that parents should limit accessibility. Increased knowledge about acceptable and actual amounts of caffeine in a single product might decrease consumption.